Current Microbial Isolates from Wound Swab and Their Susceptibility Pattern in a Private Medical College Hospital in Dhaka city - Sultana, Shahin; Mawla, Nurunnahar; Kawser, Shamima; Akhtar, Nayareen; Ali, Md Khoybar (Delta Medical College Journal, 2015)
Background: Wound infection is one of the major health problems that are caused and aggravated by the invasion of pathogenic organisms where empiric treatment is routine. Objective: To isolate and identify the bacteria causing wound infection and to determine the antimicrobial susceptibility pattern. Materials and method: A total of 263 wound swab and pus samples were collected during the period of January to December 2012 from Delta Medical College and Hospital, Dhaka, Bangladesh. Swabs from the wound were inoculated on appropriate media and cultured and the isolates were identified by standard procedures as needed. Antimicrobial susceptibility testing was performed by disk diffusion method according to The Clinical Laboratory Standard Institute guidelines. Results: In this study 220 bacterial isolates were recovered from 263 samples showing an isolation rate of 83.65%. The predominant bacteria isolated from infected wounds were Staphylococcus aureus 89 (40.45%) followed by Escherichia coli 62 (28.18%), Pseudomonas aeruginosa 34 (15.45%), Enterococci 18 (8.18%), Acinetobacter 5 (2.27%), Klebsiella 9 (4.09%) and Proteus 3 (3.36%). Staphylococcus aureus was sensitive to linezolid (94.38%), fusidic acid (91.01%), vancomycin (87.64%), amikacin (74.15%) and gentamicin (73.03%). Among the Gram negative isolates Escherichia coli was predominant and showed sensitivity to imipenem (93.54%) amikacin (83.87%) colistin (53.22%) and piperacillin and tazobactum (53.22%) and pseudomonas showed sensitivity to amikacin (73.52%), imipenem (70.58%) and colistin (70.58%). Conclusion: Staphylococcus aureus was the most frequently isolated pathogen from wound swab and the antibiotic sensitivity pattern of various isolates help to assist the clinician in appropriate selection of empirical antibiotics against wound infection. DOI: http://dx.doi.org/10.3329/dmcj.v3i1.22236 Delta Med Col J. Jan 2015; 3(1): 25-30